Representasi Profesi Jurnalis dalam Budaya Pop Korea: Analisis Resepsi Mahasiswa Jurnalis terhadap Drama Korea Pinocchio - Shania, Shania; Winduwati, Septia (Fakultas Ilmu Komunikasi Universitas Tarumanagara, 2025)
This research explores the interpretation of the journalist profession in the Korean drama Pinocchio among college students, utilizing a qualitative approach, in-depth interview method, and study of literature. Employing mass communication theory, film as a product of mass communication, reception theory, and understanding of the journalism profession, the analysis involves open coding, axial coding, and selective coding techniques. Findings reveal three main positions among students in interpreting the journalism profession, with diverse perspectives on responsibilities, ethics, and challenges in the journalistic world. The study contributes to understanding the impact of mass media dramatization on students' perceptions of the journalism profession, with implications for the development of media representations and contemporary understanding. Penelitian ini mengeksplorasi representasi profesi jurnalis dalam drama Korea Pinocchio di kalangan mahasiswa dengan pendekatan kualitatif, metode wawancara mendalam, dan studi literatur. Menggunakan teori komunikasi massa, film sebagai produk komunikasi massa, teori resepsi, dan pemahaman profesi jurnalis, analisis melibatkan teknik open coding, axial coding, dan selective coding. Temuan menunjukkan tiga posisi utama mahasiswa dalam memaknai profesi jurnalis, dengan perspektif yang beragam mengenai tanggung jawab, etika, dan tantangan di dunia jurnalistik. Hasil penelitian ini berkontribusi pada pemahaman dampak dramatization media massa terhadap persepsi mahasiswa terhadap profesi jurnalis, dengan implikasi untuk pengembangan representasi media dan pemahaman kontemporer.